Laparoscopic-assisted one-stage resection of rectal cancer with synchronous liver metastasis utilizing a pfannenstiel incision - Aljiffry, Murad (Medknow Publications & Media Pvt Ltd, 2014)
Laparoscopic approaches have been increasingly used in selected patients with either colorectal or liver cancer. However, simultaneous resection of colorectal carcinoma with synchronous liver metastases is still a subject of debate. The present case describes combined laparoscopic rectal and liver resections for a patient with primary rectal cancer and a synchronous liver metastasis utilizing a Pfannenstiel incision for specimen extraction. The operative time was 370 min and estimated blood loss was 400 mL. Postoperatively, the patient required parenteral analgesia for 48 h, resumed normal diet on day 3 and was discharged on day 7 after the operation. A laparoscopic approach utilizing a Pfannenstiel extraction incision may present an advantageous and attractive option for simultaneous laparoscopic rectal and liver resection in selected patients with the aim of improving short-term outcomes.